Decoding the role of RPL38 in lung adenocarcinoma: a multi-omics approach - Zhang, Lu; Teng, Fei; Wang, Yuan; Chen, Yang; Liu, Qiuxia; Dai, Fengsheng; Yu, Liang; Yao, Chenguo; Wang, Zhiqiang (Frontiers in Immunology, 2026)
IntroductionMembers of the Ribosomal Protein L (RPL) family are involved in diverse biological processes and cancer biology, yet their precise functions and clinical implications in lung adenocarcinoma (LUAD) remain incompletely understood.MethodsMachine learning was applied to The Cancer Genome Atlas (TCGA) data to identify pivotal RPL genes and construct a predictive risk model. Multi-omics analyses—including pan-cancer cohorts and spatial transcriptomics—were integrated to evaluate the expression and prognostic significance of Ribosomal Protein L38 (RPL38). Functional impacts were examined using CCK‑8, colony formation, wound healing, Transwell assays, and subcutaneous xenograft models.ResultsA three‑gene RPL‑based prognostic signature was established from the TCGA‑LUAD cohort. High‑risk patients exhibited shorter survival and increased immunosuppressive characteristics. RPL38 was upregulated in multiple cancers and associated with unfavorable outcomes. Immunohistochemical and spatial transcriptomic analyses confirmed its aberrant expression in LUAD and linked it to an immunosuppressive tumor microenvironment. Genetic ablation of RPL38 significantly inhibited LUAD cell proliferation and migration in vitro, and impaired xenograft tumor growth in vivo.ConclusionsRPL38 plays a tumor‑promoting role in LUAD. This study clarifies the contribution of RPL38 to LUAD development, provides new insights into its pathogenesis, and suggests a rationale for therapeutic targeting of RPL38 in LUAD treatment.